IDENTIFICATION OF SOIL FUNGI ISOLATED FROM ALFALFA (Medicago sativa L) TO FIND SPECIFIC FUNGI WHICH IMPROVED THE GROWTH OF ALFALFA - Yudiarti, T.; Sumarsono, S.; Widjayanto, D.W. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
Objective of the study was to identify all kinds of fungi which can life in the alfalfa plantation inBaturaden Purwokerto-Central Java. Fungi used in this study was 38 isolates. All fungi have been takenfrom the isolation of soil and root of diseased plant. Macroscopic and microscopic methods were usedfor identification. Potato Dextrose Agar (PDA) medium was used to grow the fungi. All fungi wereidentified using book identification of fungi. The results showed that from 38 isolates, six species wasdetermined and one was unidentifed. Those species identified were Cuninghammela sp, Trichoderma sp,Vertilicium sp, Eupenicillium sp, Pythium sp, Aspergillus sp.